2020
DOI: 10.1017/cjn.2020.136
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Herniation of the Gyrus Rectus Resulting in Compressive Optic Neuropathy

Abstract: We report a 34-year-old male with a previously uninvestigated lifelong blindness of the right eye from compressive optic neuropathy secondary to congenital herniation of the gyrus rectus (HGR). His past medical history was otherwise unremarkable, with no history of prior head or ocular trauma. On examination, he had no light perception in the right eye, right relative afferent pupillary defect (RAPD), and primary optic atrophy. His left eye had normal visual acuity, color vision, and a healthy optic disc. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In contrast, our patients reported subacute vision loss with optic nerve head pallor, typical of compressive optic neuropathy. More recently, Gilani et al (2) reported a man with previously unexplained unilateral blindness since birth. Neuroimaging revealed inferior herniation of the ipsilateral gyrus rectus compressing the optic nerve, which was inferred to be the cause of visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our patients reported subacute vision loss with optic nerve head pallor, typical of compressive optic neuropathy. More recently, Gilani et al (2) reported a man with previously unexplained unilateral blindness since birth. Neuroimaging revealed inferior herniation of the ipsilateral gyrus rectus compressing the optic nerve, which was inferred to be the cause of visual loss.…”
Section: Discussionmentioning
confidence: 99%